Latvian SSR MGB Special Troops and Special Agents Against National Armed Units in 1946–1953 - Jansons , Ritvars (Genocidas ir rezistencija, 1997)
To suppress the Latvian national resistance movement, the Soviet state security organs had to take special measures. It has been established that the state security organs were able to crush the national resistance movement most effectively not by direct military operations, but by using clandestine methods of operative work. From 1 March 1947, the MGB was given the task of combating the nationalist underground, for which purpose Division 2–N was set up. The operational activity of the state security organs of the Latvian SSR was impossible without an agency, and the fight against the national partisans – without special agents and groups made up of agents–hitmen.
Keywords: Latvia; agents; armed resistance; KGB methods; repression structures